Cultivating User-ship? Developing a Circular System for the Acquisition and Use of Baby Clothing. (4th May 2017) - Petersen, Trine Brun; Riisberg, Vibeke
Abstract: This paper sets out to explore the significance of the production, sale and consumption of clothing as a product service system rather than as the more familiar "shop-window" product offered for individual sale. While there are a number of studies of occupational clothing systems, relatively little is known about clothing systems tailored for the private market. This article presents a case study of a recently launched subscription service for baby clothing, which offered a range of eco-certified garments for rent as more or less complete wardrobes. Drawing on fashion scholar Kate Fletcher's concept of "techniques and processes of use" and on Actor-Network Theory, the study follows the company from its tentative beginnings through its first year in a process that provided an opportunity to study a clothing system "in the making." Particular interest is paid to how the leasing system and product design features are mutually constitutive and to how the system interconnects with practices of use and maintenance among subscribers with a special interest in laundry regimes and durability. Taking this empirical example as its point of departure, the article concludes with a discussion of how product qualities and processes of use are intertwined and co-constructed.